A clinical case of exocrine pancreatic insufficiency in a patient with type 1 diabetes mellitus - M. R. Ragimov; T. V. Nikonova; E. V. Marchenko; N. M. Malysheva; O. S. Derevyanko (Сахарный диабет, 2023)
The pancreas belongs to the glands of mixed secretion and simultaneously performs both endo- and exocrine functions. Exocrine pancreatic insufficiency (EPI) is the general name for the malabsorption process caused by inadequate production and decreased activation of the enzymes of the pancreas acinar cells, such as amylase, lipase and protease, which are necessary for digestion. The prevalence of EPI in patients with type 1 diabetes, according to many authors, varies from 25 to 59%, which is determine by the data of pancreatic elastase-1. In this work, we present a clinical case of confirmed exocrine pancreatic insufficiency in a patient with a 6-year history of type 1 diabetes, which became the main cause of the development of episodes of hypoglycemia after meals. In the course of further studies, antibodies to lactoferrin and a reduced prostate volume, determined by MRI data, high levels of antibodies to glutamate decarboxylase and zinc co-transporter 8, as well as residual insulin secretion based on the level of C-peptide on an empty stomach detected.